2010
DOI: 10.1111/j.1365-2559.2010.03646.x
|View full text |Cite
|
Sign up to set email alerts
|

RET rearrangements and BRAF mutation in undifferentiated thyroid carcinomas having papillary carcinoma components

Abstract: The high frequency of BRAF mutation and the absence of RET rearrangements in UC components from composite UCs supports the hypothesis that UCs may actually represent progressive malignant degeneration of a BRAF-mutated, well-differentiated thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
3
13
1
7
Order By: Relevance
“…The RET/PTC rearrangement has been investigated in many studies. No RET/PTC arrangement was detected in benign lesions such as nodular hyperplasias and follicular adenomas in our study, as was the case with most of the studies in the literature (8,27,48).…”
Section: Discussionsupporting
confidence: 67%
“…The RET/PTC rearrangement has been investigated in many studies. No RET/PTC arrangement was detected in benign lesions such as nodular hyperplasias and follicular adenomas in our study, as was the case with most of the studies in the literature (8,27,48).…”
Section: Discussionsupporting
confidence: 67%
“…Unlike BRAF and RAS mutations, RET/ PTC1 rearrangements are associated with a very low probability of dedifferentiation in papillary carcinomas [31,37,92]. The RET/PTC3 rearrangement, however, may predispose to dedifferentiation and more aggressive biologic behavior [93,94].…”
Section: Prognostic Molecular Markers In Thyroid Cancermentioning
confidence: 99%
“…Moreover, RET/PTC-positive PDTC are not associated with increased aggressiveness or poor patient survival and usually show histological evidence indicating coexistence with or possible evolution from a PTC often diagnosed as a classic, solid or tall cell variant PTC [7, 22, 57]. Concerning UTC, all previous studies reported an absence of RET/PTC rearrangements in this setting [22, 58]; only the study by Mochizuki et al [59], who studied seven composite UTC (UTC having a PTC component) and 14 single component UTC, has found the presence of a RET/PTC3 rearrangement in both components (UTC and PTC) of one composite UTC, whereas all 14 single component UTC were RET/PTC-negative. …”
Section: Ret/ptc and Pax8/pparγ Rearrangements In Pdtc And Utcmentioning
confidence: 99%